Cells and Batteries
By using negative electrode sheets with different adhesive formulations in the inner and outer layers of the battery cell, the problem of huge adhesion in the thickness direction of the battery cell is solved, better electrolyte wetting and flexibility in the negative electrode sheet are achieved, reducing the DC internal resistance of the battery, and improving the circulation performance and production efficiency.
Patent Information
- Application Number
- CN202411854296.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The existing battery cells have a huge adhesion gap in the thickness direction, resulting in high internal stress and poor electrolyte wetting, which increases the risk of interfacial lithium analysis.
Negative electrode sheets with different adhesive formulations are used in the inner and outer layers of the battery cell respectively. By adjusting the swelling rate and mass percentage of the adhesive, the bonding effect of the negative electrode sheet and the separator, the electrolyte wetting and production efficiency are balanced.
By optimizing the adhesive formulation, the wetting property of the electrolyte and the flexibility of the negative electrode sheet are improved, the DC internal resistance of the battery is reduced, the circulation performance is improved, and the overall production efficiency is improved.
Smart Images

Figure CN119340397B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to battery cells and batteries. Background Art
[0002] In order to increase the energy density of the battery cell, the size of the battery cell is getting bigger and bigger, and the thickness of the battery cell is getting thicker and thicker. Relatively speaking, the outer electrode of the battery cell is easier to be infiltrated with the electrolyte, and it is easier to have good adhesion with the glue-coated diaphragm (when the core is hot-pressed, the glue coating on the outer diaphragm is heated first, and it is easier to bond with the glue layer on the diaphragm under pressure, while the temperature of the diaphragm glue layer close to the inner layer of the core is relatively lower, and the coating and the negative electrode are relatively poorer), while the inner electrode is more difficult to be infiltrated with the electrolyte (after injection, the electrolyte preferentially infiltrates the negative electrode near the outer layer of the core, while the diffusion of the electrolyte in the inner layer becomes difficult, and it is more difficult to infiltrate the negative electrode), and it is more difficult to have good adhesion with the glue-coated diaphragm, so the inner layer of the core has a relatively high risk of interfacial lithium precipitation due to poor wettability, and the bonding effect of the negative electrode of the core will be deviated.
[0003] The current formula of the negative electrode sheets for the outer and inner layers of the battery cell is the same, and the coating process is also the same, which makes it relatively more difficult for the electrolyte to penetrate into the inner layer of the negative electrode sheet; and the adhesion between the inner layer of the negative electrode sheet and the coated separator is also worse, but the adhesion of the outer layer is relatively large, resulting in a large disparity in adhesion across the entire thickness, and relatively high internal stress. Currently, the main method to improve the wettability of the inner layer of the negative electrode sheet is to increase the standing time after the battery cell is injected, which will relatively affect the efficiency, and to increase the hot pressing time of the battery cell to improve the adhesion of the inner layer of the negative electrode sheet, which will also affect the hot pressing time. Summary of the invention
[0004] In view of this, the present invention provides a battery cell and a battery in which the negative electrode sheet active material layers corresponding to the inner layer area and the outer layer area of the battery cell adopt different adhesive formulations, thereby balancing the bonding effect of the negative electrode sheet and the separator inside the entire core package, the electrolyte wettability and the production efficiency.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] In a first aspect, the present invention provides a battery cell, which includes a battery cell inner region 100 and a battery cell outer region 200 from the center to the edge of the battery cell;
[0007] The battery cell includes a negative electrode sheet 10, a positive electrode sheet 20 and a separator 30. The negative electrode sheet 10 includes a first negative electrode sheet 11 and a second negative electrode sheet 12. The first negative electrode sheet 11 is arranged in the inner layer area 100 of the battery cell, and the second negative electrode sheet 12 is arranged in the outer layer area 200 of the battery cell.
[0008] The first negative electrode sheet includes a first active material layer, and the first active material layer includes a first active material and a first binder;
[0009] The second negative electrode sheet includes a second active material layer, and the second active material layer includes a second active material and a second binder;
[0010] The swelling rate of the first binder is greater than the swelling rate of the second binder;
[0011] The bonding force between the first negative electrode sheet and the separator is recorded as A1, and the bonding force between the second negative electrode sheet and the separator is recorded as A2. A1 and A2 satisfy the following relationship:
[0012] -2≤A1-A2≤0.
[0013] In an embodiment of the present invention, the first adhesive includes a Class B adhesive, or includes a Class B adhesive and a Class C adhesive;
[0014] The second adhesive includes a Class C adhesive, or includes a Class B adhesive and a Class C adhesive;
[0015] The mass percentage of the type B adhesive in the first adhesive is greater than the mass percentage of the type B adhesive in the second adhesive, and the swelling rate of the type B adhesive is greater than the swelling rate of the type C adhesive.
[0016] Preferably, the swelling ratio of the type B binder is 40% to 75%.
[0017] Preferably, the swelling rate of the C-type adhesive is 0% to 20%.
[0018] Preferably, the adhesion between the first negative electrode sheet and the separator is 4.0-6.0 N / m.
[0019] Preferably, the bonding strength between the second negative electrode sheet and the separator is 6.0 to 8.0 N / m.
[0020] In an embodiment of the present invention, the type B binder includes at least one of 2-ethylhexyl acrylate modified styrene-butadiene rubber, acrylamide modified styrene-butadiene rubber, methyl acrylate modified styrene-butadiene rubber, butyl acrylate modified styrene-acrylic rubber, acrylonitrile modified styrene-acrylic rubber, and epoxy acrylate modified styrene-acrylic rubber.
[0021] In an embodiment of the present invention, the Class C adhesive includes at least one of an acrylate, acrylic acid, and acrylonitrile ternary copolymer adhesive, an acrylic acid, acrylamide, and acrylonitrile ternary copolymer adhesive, an acrylic acid, an acrylate, and an acrylamide ternary copolymer adhesive, a methyl acrylate, butadiene, acrylic acid, and acrylonitrile tetrapolymer adhesive, and an acrylic acid, epoxypropylene, and acrylate ternary copolymer adhesive.
[0022] Preferably, in terms of mass percentage, the first adhesive comprises: 20% to 100% of a type B adhesive and 0% to 80% of a type C adhesive.
[0023] Preferably, the second binder comprises, by mass percentage, 0-55% of a type B binder and 45%-100% of a type C binder.
[0024] Preferably, the first active material layer includes, by weight, 95 to 99 parts of the first active material, 1.0 to 3.5 parts of the first binder, 0.5 to 2.0 parts of the first conductive agent, and 0 to 1.5 parts of the first thickener.
[0025] Preferably, the first active material layer includes, by weight, 95 to 98.5 parts of the first active material, 1.0 to 3.0 parts of the first binder, 0.5 to 1.5 parts of the first conductive agent, and 0 to 1.2 parts of the first thickener.
[0026] Preferably, the second active material layer includes, by weight, 95 to 99 parts of the second active material, 0.5 to 3.5 parts of the second binder, 0.5 to 2.0 parts of the second conductive agent, and 0 to 1.5 parts of the second thickener.
[0027] Preferably, the second active material layer includes, by weight, 95.5 to 99 parts of the second active material, 1.0 to 3.0 parts of the second binder, 0.5 to 1.5 parts of the second conductive agent, and 0 to 1.2 parts of the second thickener.
[0028] In an embodiment of the present invention, the mass percentage of the first binder in the first active material layer is greater than or equal to the mass percentage of the second binder in the second active material layer.
[0029] In an embodiment of the present invention, the inner layer area of the battery cell accounts for 10% to 75% of the overall thickness of the battery cell.
[0030] In an embodiment of the present invention, the battery cell is a wound battery cell or a laminated battery cell.
[0031] In a second aspect, the present invention provides a battery comprising the above-mentioned battery cell.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] In the present invention, the first negative electrode sheet arranged in the inner layer area of the battery core includes a first binder, and the second negative electrode sheet in the outer layer area of the battery core includes a second binder. Among them, the first binder has a higher swelling rate and a stronger adhesive force, so that the electrode sheet has better wettability with the electrolyte, and the corresponding negative electrode sheet has better flexibility, and it is easier to anchor and bond with the diaphragm during hot pressing, thereby reducing the DC internal resistance of the battery, which is beneficial to improving the cycle performance of the battery; the swelling rate and adhesive force of the second binder are smaller, and the second binder makes the second negative electrode sheet relatively poor in wettability with the electrolyte, but because the diffusion distance of the electrolyte infiltration is shorter, it can meet the wettability requirements, and the corresponding electrode sheet has some flexibility deviation, and it heats up faster during hot pressing, and it is easier to bond with the diaphragm. Therefore, the present invention can ultimately achieve comprehensive production efficiency, balance the bonding effect of the negative electrode sheet and the diaphragm inside the entire core package, the electrolyte wettability and the production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is the division of the inner and outer areas of the wound battery cell.
[0035] Figure 2 It is the division of the inner and outer areas in the laminated battery cell.
[0036] Figure 3 It is a schematic diagram of the structure of the negative electrode sheet of the present invention that has not been cut or wound.
[0037] Figure 4 It is a schematic diagram of the structure of the wound battery cell of the present invention.
[0038] The reference numerals are as follows:
[0039] 100: inner area of the battery cell;
[0040] 200: outer area of the battery cell;
[0041] 300: vertical center axis;
[0042] 10: Negative electrode
[0043] 11: first negative electrode sheet;
[0044] 12: second negative electrode sheet;
[0045] 20: positive electrode;
[0046] 30: Diaphragm. DETAILED DESCRIPTION
[0047] The present invention discloses a cell and a battery, and those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.
[0048] In the description of the present invention, it should be noted that the terms "first", "second", etc. are only used for descriptive purposes, and do not indicate or imply relative importance.
[0049] In the description of the present invention, a list of items connected by the term "at least one of" or other similar terms may mean any combination of the listed items. For example, if items A, B are listed, the phrase "at least one of A, B" means only A; only B; or A and B. In another example, if items A, B, C are listed, the phrase "at least one of A, B, C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0050] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range or the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0051] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0052] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0053] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0054] Specifically, the present invention adopts the following technical solutions:
[0055] In a first aspect, the present invention provides a battery cell, which includes a battery cell inner region 100 and a battery cell outer region 200 from the center to the edge of the battery cell;
[0056] The battery cell includes a negative electrode sheet 10, a positive electrode sheet 20 and a separator 30. The negative electrode sheet 10 includes a first negative electrode sheet 11 and a second negative electrode sheet 12. The first negative electrode sheet 11 is arranged in the inner layer area 100 of the battery cell, and the second negative electrode sheet 12 is arranged in the outer layer area 200 of the battery cell.
[0057] The first negative electrode sheet includes a first active material layer, and the first active material layer includes a first active material and a first binder;
[0058] The second negative electrode sheet includes a second active material layer, and the second active material layer includes a second active material and a second binder;
[0059] The swelling rate of the first binder is greater than the swelling rate of the second binder;
[0060] The bonding force between the first negative electrode sheet and the separator is recorded as A1, and the bonding force between the second negative electrode sheet and the separator is recorded as A2. A1 and A2 satisfy the following relationship:
[0061] -2≤A1-A2≤0.
[0062] In an embodiment of the present invention, Figure 1 and Figure 2 As shown, the inner region 100 of the battery core refers to the region close to the vertical center axis 300 of the battery core, and the outer region 200 of the battery core refers to the region away from the vertical center axis 300 of the battery core. For example, the battery core is a wound battery core, such as Figure 1 As shown, the inner region 100 of the battery cell refers to the region closer to the vertical center axis 300 in the multilayer structure of the winding structure after the pole piece is wound along the vertical center axis 300 to form a winding structure, and accounts for 10% to 75% of the overall thickness of the battery cell (denoted as H). The outer region 200 of the battery cell refers to the region farther from the vertical center axis 300 of the winding structure, and accounts for 25% to 90% of the overall thickness of the battery cell. For example, the battery cell is a laminated battery cell, such as Figure 2 As shown, the inner region 100 of the battery cell refers to the region closer to the vertical center axis 300 in the multilayer structure of the stacked structure after the pole pieces are stacked along the vertical center axis 300 to form a stacked structure, and occupies 10% to 75% of the overall thickness of the battery cell (denoted as H). The outer region 200 of the battery cell refers to the region farther from the vertical center axis 300 of the stacked structure, and occupies 25% to 90% of the overall thickness of the battery cell.
[0063] In the prior art, it is more difficult for the electrolyte to penetrate into the negative electrode sheet in the inner layer of the battery cell compared to the negative electrode sheet in the outer layer of the battery cell, and the adhesion between the negative electrode sheet in the inner layer of the battery cell and the adhesive diaphragm is also worse, but the adhesion between the negative electrode sheet in the outer layer of the battery cell and the adhesive diaphragm is larger, resulting in a large disparity in adhesion across the entire thickness and relatively high internal stress. In the present invention, the first negative electrode sheet disposed in the inner layer of the battery cell includes a first binder, and the outer layer of the battery cell includes a second binder. Among them, the first binder has more polar functional groups, which is conducive to mutual diffusion with the PVDF molecular chains in the diaphragm, improving the swelling rate and adhesion, making the electrode sheet better infiltrative with the electrolyte, and the corresponding negative electrode sheet has better flexibility, and is easier to anchor and bond with the diaphragm during hot pressing, thereby reducing the DC internal resistance of the battery, which is beneficial to improving the battery's cycle performance; the swelling rate and adhesion of the second binder are smaller. This binder makes the electrode sheet relatively less wettable with the electrolyte, but because the diffusion distance of the electrolyte infiltration is shorter, it can meet the wettability requirements, and the corresponding electrode sheet has some flexibility deviation, and it heats up faster during hot pressing, and is easier to bond with the diaphragm.
[0064] In an embodiment of the present invention, the value of A1-A2 is -2 to 0. Exemplarily, the value of A1-A2 is any value among -2, -1.9, -1.7, -1.5, -1.3, -1.1, -1, -0.9, -0.7, -0.5, -0.3, -0.1, 0 or any value within the range consisting of any two of the above values.
[0065] In the embodiment of the present invention, the first adhesive includes a Class B adhesive, or includes a Class B adhesive and a Class C adhesive; the second adhesive includes a Class C adhesive, or includes a Class B adhesive and a Class C adhesive; and the mass percentage of the Class B adhesive in the first adhesive is greater than the mass percentage of the Class B adhesive in the second adhesive, and the swelling rate of the Class B adhesive is greater than the swelling rate of the Class C adhesive. When this condition is met, it can be ensured that the swelling rate of the first adhesive is greater than the swelling rate of the second adhesive.
[0066] Preferably, the swelling rate of the type B binder is 40% to 75%. Exemplarily, the swelling rate of the type B binder is any value among 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, or any value within the range consisting of any two of the above values.
[0067] Preferably, the swelling rate of the C-type adhesive is 0% to 20%. Exemplarily, the swelling rate of the C-type adhesive is any value among 0%, 3%, 6%, 9%, 12%, 15%, 18%, 20%, or any value within the range consisting of any two of the above values.
[0068] Preferably, the adhesion between the first negative electrode sheet and the separator is 4.0-6.0 N / m. Exemplarily, the adhesion between the first negative electrode sheet and the separator is any value among 4.0 N / m, 4.2 N / m, 4.4 N / m, 4.6 N / m, 4.8 N / m, 5.0 N / m, 5.2 N / m, 5.4 N / m, 5.6 N / m, 5.8 N / m, 6.0 N / m or any value within the range consisting of any two of the above values.
[0069] Preferably, the bonding strength between the second negative electrode sheet and the separator is 6.0 to 8.0 N / m. Exemplarily, the bonding strength between the second negative electrode sheet and the separator is any value among 6.0 N / m, 6.2 N / m, 6.4 N / m, 6.6 N / m, 6.8 N / m, 7.0 N / m, 7.2 N / m, 7.4 N / m, 7.6 N / m, 7.8 N / m, and 8.0 N / m, or any value within the range consisting of any two of the above values.
[0070] In an embodiment of the present invention, the B-type binder includes at least one of acrylate isooctyl modified styrene butadiene rubber (swelling rate of 49% to 52%), acrylamide modified styrene butadiene rubber (swelling rate of 43% to 47%), methyl acrylate modified styrene butadiene rubber (swelling rate of 43% to 47%), butyl acrylate modified styrene acrylic rubber (swelling rate of 70% to 75%), acrylonitrile modified styrene acrylic rubber (swelling rate of 57% to 64%), and epoxy acrylate modified styrene acrylic rubber (swelling rate of 65% to 69%). The B-type binder has more polar functional groups, which is conducive to forming a stronger hydrogen bond interaction with the coating molecules on the glue-coated diaphragm, thereby improving the bonding force with the glue-coated diaphragm. In addition, the electrolyte swelling rate corresponding to the B-type binder is higher than that of the conventional C-type binder, which is conducive to improving the wettability of the electrode and the electrolyte, thereby reducing the DC internal resistance of the battery and improving the cycle performance of the battery.
[0071] In an embodiment of the present invention, the Class C adhesive includes at least one of an acrylate, acrylic acid, and acrylonitrile ternary copolymer adhesive (swelling rate of 15% to 20%), an acrylic acid, acrylamide, and acrylonitrile ternary copolymer adhesive (swelling rate of 0% to 3%), an acrylic acid, an acrylate, and an acrylamide ternary copolymer adhesive (swelling rate of 3% to 6%), a methyl acrylate, butadiene, acrylic acid, and acrylonitrile quaternary copolymer adhesive (swelling rate of 6% to 9%), and an acrylic acid, epoxypropylene, and an acrylate ternary copolymer adhesive (swelling rate of 9% to 15%).
[0072] Preferably, in terms of mass percentage, the first adhesive includes 20% to 100% of the B-type adhesive and 0 to 80% of the C-type adhesive. Exemplarily, the first adhesive includes 20% of the B-type adhesive and 80% of the C-type adhesive; or the first adhesive includes 40% of the B-type adhesive and 60% of the C-type adhesive; or the first adhesive includes 60% of the B-type adhesive and 40% of the C-type adhesive; or the first adhesive includes 80% of the B-type adhesive and 20% of the C-type adhesive; or the first adhesive includes 100% of the B-type adhesive and 0% of the C-type adhesive.
[0073] Preferably, the second adhesive includes 0-55% of Class B adhesive and 45%-100% of Class C adhesive. Exemplarily, the second adhesive includes 0% of Class B adhesive and 100% of Class C adhesive; or the second adhesive includes 10% of Class B adhesive and 90% of Class C adhesive; or the second adhesive includes 20% of Class B adhesive and 80% of Class C adhesive; or the second adhesive includes 30% of Class B adhesive and 70% of Class C adhesive; or the second adhesive includes 40% of Class B adhesive and 60% of Class C adhesive; or the second adhesive includes 50% of Class B adhesive and 50% of Class C adhesive; or the second adhesive includes 55% of Class B adhesive and 45% of Class C adhesive.
[0074] Preferably, in parts by mass, the first active material layer includes 95-99 parts of the first active material, 1.0-3.5 parts of the first binder, 0.5-2.0 parts of the first conductive agent, and 0-1.5 parts of the first thickener. Exemplarily, the first active material layer includes 96 parts of the first active material, 2 parts of the first binder, 1 part of the first conductive agent, and 1 part of the first thickener, or the first active material layer includes 95 parts of the first active material, 3.5 parts of the first binder, 0.5 parts of the first conductive agent, and 1.5 parts of the first thickener, or the first active material layer includes 99 parts of the first active material, 1 part of the first binder, 2 parts of the first conductive agent, and 0 parts of the first thickener.
[0075] Preferably, the first active material layer includes, by weight, 95 to 98.5 parts of the first active material, 1.0 to 3.0 parts of the first binder, 0.5 to 1.5 parts of the first conductive agent, and 0 to 1.2 parts of the first thickener.
[0076] Preferably, the second active material layer includes 95-99 parts of the second active material, 0.5-3.5 parts of the second binder, 0.5-2.0 parts of the second conductive agent, and 0-1.5 parts of the second thickener, by weight. Exemplarily, the second active material layer includes 96.5 parts of the second active material, 1.5 parts of the second binder, 1 part of the second conductive agent, and 1 part of the second thickener, or the second active material layer includes 95 parts of the second active material, 3.5 parts of the second binder, 0.5 parts of the second conductive agent, and 1.5 parts of the second thickener, or the second active material layer includes 99 parts of the second active material, 0.5 parts of the second binder, 2 parts of the second conductive agent, and 0 parts of the second thickener.
[0077] Preferably, the second active material layer includes, by weight, 95.5 to 99 parts of the second active material, 1.0 to 3.0 parts of the second binder, 0.5 to 1.5 parts of the second conductive agent, and 0 to 1.2 parts of the second thickener.
[0078] In an embodiment of the present invention, the mass percentage of the first binder in the first active material layer is greater than or equal to the mass percentage of the second binder in the second active material layer. In an embodiment of the present invention, for different types of active materials, the first active material layer or the first active material layer may choose to add or not add a thickener. For example, a negative electrode active material with a small particle size or a small specific surface area that is not easy to disperse needs to add a thickener, while a negative electrode active material with a large particle size or a relatively large specific surface area that is easy to disperse does not need to add a thickener.
[0079] In an embodiment of the present invention, the inner layer area of the battery cell accounts for 10% to 75% of the overall thickness of the battery cell. Exemplarily, the inner layer area of the battery cell accounts for any value of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 75% of the overall thickness of the battery cell, or any value within the range of any two of the above values.
[0080] Preferably, the thickness of the first active material layer and the second active material layer is independently 40 to 260 μm. Exemplary values are any of 40 μm, 60 μm, 80 μm, 100 μm, 140 μm, 180 μm, 220 μm, and 260 μm, or any value within the range of any two of the above values. The thicker the coating thickness of the active material layer, the more conducive it is to reducing the internal resistance of the battery cell, preferably 100 to 260 μm, and more preferably 180 to 260 μm.
[0081] In the embodiment of the present invention, the thicknesses of the first active material layer and the second active material layer may be the same or different.
[0082] In an embodiment of the present invention, the first active material layer or the second active material layer is disposed on one side or both sides of the positive electrode current collector.
[0083] In an embodiment of the present invention, the negative electrode current collector is copper foil.
[0084] Preferably, the thickness of the negative electrode current collector is 6 to 20 μm. Exemplarily, the thickness of the negative electrode current collector is any value among 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, or any value within the range of any two of the above values.
[0085] In an embodiment of the present invention, the first active material and the second active material independently include at least one of graphite, soft carbon, hard carbon, amorphous carbon, carbon fiber, and mesophase carbon microspheres.
[0086] In an embodiment of the present invention, the first conductive agent and the second conductive agent independently include at least one of conductive carbon black, carbon nanotubes, graphene, and carbon nanofibers.
[0087] In an embodiment of the present invention, the first thickener and the second thickener independently include at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxyethyl cellulose, lithium carboxyethyl cellulose, sodium carboxymethyl cellulose modified with acrylate flexible chain, and lithium carboxymethyl cellulose modified with acrylate flexible chain.
[0088] In the embodiment of the present invention, the battery cell is a wound battery cell or a laminated battery cell. The specific embodiment of the present invention exemplifies a wound battery cell, but is not limited to a wound battery cell. A laminated battery cell can also implement the present invention.
[0089] In an embodiment of the present invention, the battery cell is a wound battery cell, the first negative electrode sheet and the second negative electrode sheet form a complete electrode sheet, and the current collectors used by the first negative electrode sheet and the second negative electrode sheet are a continuous whole, except that the active material layer components of the first negative electrode sheet and the second negative electrode sheet are different. Alternatively, the current collectors used by the first negative electrode sheet and the second negative electrode sheet are two independent entities. Alternatively, the first negative electrode sheet includes multiple first sub-negative electrode sheets, and the current collectors of the multiple first sub-negative electrode sheets are multiple independent entities, and the second negative electrode sheet includes multiple second sub-negative electrode sheets, and the current collectors of the multiple second sub-negative electrode sheets are multiple independent entities.
[0090] In an embodiment of the present invention, the battery cell is a stacked battery cell, the first negative electrode sheet includes a plurality of first sub-negative electrode sheets, and the second negative electrode sheet includes a plurality of second sub-negative electrode sheets.
[0091] In a second aspect, the present invention provides a battery comprising the above-mentioned battery cell.
[0092] In the embodiment of the present invention, the battery further comprises a positive electrode sheet, a separator, and an electrolyte. The present application has no particular limitation on the positive electrode sheet, the separator, and the electrolyte in the battery, and those skilled in the art can select them according to actual needs as long as the purpose of the present application can be achieved.
[0093] In the embodiment of the present invention, the battery is a lithium ion battery, but is not limited to lithium ion batteries. Other batteries such as sodium ion batteries, potassium ion batteries, lithium sulfur batteries, zinc ion batteries, etc. can also implement the present invention.
[0094] In the embodiment of the present invention, the battery structure includes but is not limited to button batteries, soft-pack batteries, cylindrical batteries, etc.
[0095] The reagents, instruments or materials used in the present invention can be obtained through commercial channels. The binders or modified binders used in the following examples are purchased from Arkema, Sinochem Blue Sky, East Sunshine and other companies.
[0096] The present invention will be further described below in conjunction with embodiments:
[0097] Example 1
[0098] The method for preparing the lithium ion secondary battery of this embodiment comprises the following steps:
[0099] (1) Preparation of negative electrode sheet:
[0100] ① First negative electrode slurry: 96.5 parts of negative electrode active material (graphite), 1 part of conductive agent (conductive carbon black), 0.75 parts of type B binder (isooctyl acrylate modified styrene-butadiene rubber), 0.75 parts of type C binder (acrylate, acrylic acid, acrylonitrile ternary copolymer binder), 1 part of thickener (sodium carboxymethyl cellulose CMC), add deionized water, mix and stir to obtain the first negative electrode slurry with a solid content of 50%, a viscosity of 2000 mPa·s, and a fineness of 30μm;
[0101] ② Second negative electrode slurry: 96.5 parts of negative electrode active material graphite, 1 part of conductive agent (conductive carbon black), 0 parts of type B binder, 1.5 parts of type C binder (acrylate, acrylic acid, acrylonitrile ternary copolymer binder), and 1 part of thickener CMC are mixed, deionized water is added, and after mixing and stirring, a second negative electrode slurry with a solid content of 50%, a viscosity of 2000 mPa·s, and a fineness of 30μm is obtained;
[0102] ③ The first negative electrode slurry and the second negative electrode slurry are gradually extruded and coated on the electrode foil to form the first negative electrode sheet and the second negative electrode sheet on the complete electrode sheet roll (when preparing the roll core, the first negative electrode sheet is arranged in the inner layer area of the roll core, and the second negative electrode sheet is arranged in the outer layer area of the roll core), dried, rolled, and then slit and sliced to obtain the negative electrode sheet. The structural diagram is shown in Figure 3 shown.
[0103] (2) Preparation of positive electrode:
[0104] 97.0 parts of lithium cobalt oxide, a positive electrode active material, 1 part of conductive carbon black SP, 0.2 parts of polyether-modified acrylate, and 1.8 parts of hexafluoropropylene-modified PVDF were mixed, and an appropriate amount of N-methylpyrrolidone (NMP) was added and stirred to obtain a positive electrode slurry with a solid content of 63.1%, a viscosity of 9540 mPa·s, and a fineness of 10μm. The positive electrode slurry was extruded and coated on the electrode foil, dried, rolled, and then slit and sliced to obtain a positive electrode sheet.
[0105] (3) Diaphragm:
[0106] The diaphragm is 9+3+3+3 (3μm alumina ceramic coated on one side and 3μm PVDF coated on both sides).
[0107] (4) Battery assembly:
[0108] The positive electrode sheet, the negative electrode sheet, and the separator are wound to obtain a bare battery cell. The first negative electrode sheet is arranged in the inner layer area of the winding core, and the inner layer area of the winding core accounts for 50% of the overall thickness of the winding core. The second negative electrode sheet is arranged in the outer layer area of the winding core (such as Figure 4 The positive and negative poles are welded, the bare cell is packed in an aluminum-plastic film battery case (or an aluminum battery case / steel battery case / nickel-plated battery case), liquid is injected, packaged, left to stand, formed, and capacity is divided to obtain a lithium-ion secondary battery.
[0109] Example 2
[0110] The only difference between this embodiment and embodiment 1 is that the type B binder of the negative electrode sheet is replaced with acrylamide-modified styrene-butadiene rubber.
[0111] Example 3
[0112] The only difference between this embodiment and embodiment 1 is that the type B binder of the negative electrode sheet is replaced with butyl acrylate modified styrene acrylic rubber.
[0113] Example 4
[0114] The only difference between this embodiment and embodiment 1 is that the type B binder of the negative electrode sheet is replaced with acrylonitrile-modified styrene-acrylic rubber.
[0115] Example 5
[0116] The only difference between this embodiment and embodiment 1 is that the amount of type B binder and type C binder used in the first negative electrode sheet and the second negative electrode sheet is different.
[0117] In the first negative electrode sheet, there are 0.3 parts of type B binder and 1.2 parts of type C binder, and the type B binder accounts for 20%;
[0118] In the second negative electrode sheet, there are 0.15 parts of Class B binder and 1.35 parts of Class C binder, and Class B binder accounts for 10%.
[0119] Example 6
[0120] The only difference between this embodiment and embodiment 1 is that the amount of type B binder and type C binder used in the first negative electrode sheet and the second negative electrode sheet is different.
[0121] In the first negative electrode sheet, there are 1.5 parts of type B binder and 0 parts of type C binder, and the type B binder accounts for 100%;
[0122] In the second negative electrode sheet, there are 0.825 parts of Class B binder and 0.675 parts of Class C binder, and Class B binder accounts for 55%.
[0123] Example 7
[0124] The only difference between this embodiment and Embodiment 1 is that the inner layer area of the core accounts for 10% of the overall thickness of the core.
[0125] Example 8
[0126] The only difference between this embodiment and Embodiment 1 is that the inner layer area of the core accounts for 75% of the overall thickness of the core.
[0127] Comparative Example 1
[0128] The only difference between this comparative example and Example 1 is the preparation of the negative electrode sheet, which is prepared as follows:
[0129] 96.5 parts of negative electrode active material (graphite), 1 part of conductive agent (conductive carbon black), 0 parts of type B binder, 1.5 parts of type C binder (acrylate, acrylic acid, acrylonitrile ternary copolymer binder), and 1 part of thickener CMC were mixed, deionized water was added, and after mixing and stirring, a negative electrode slurry with a solid content of 50%, a viscosity of 2000 mPa·s, and a fineness of 30μm was obtained;
[0130] The negative electrode slurry is extruded and coated on the electrode foil, dried, rolled, and then slit and sliced to obtain the negative electrode sheet.
[0131] Performance Testing
[0132] The negative electrode sheets and batteries of the above embodiments and comparative examples were subjected to performance tests, including:
[0133] (1) Liquid absorption time test:
[0134] Take the negative electrode sheet and use a micropipette to drop 10μL of electrolyte on the negative electrode sheet. Test the time when the electrolyte completely disappears from the electrode sheet, which is recorded as the absorption time. The longer the absorption time, the worse the wettability of the corresponding negative electrode sheet and the electrolyte.
[0135] (2) Diaphragm and electrode adhesion test:
[0136] Cut the separator and the negative electrode into 15 cm wide samples, gently peel off one end of the separator, clamp it vertically on the tensile instrument, and test the adhesion between the separator and the electrode at 180°.
[0137] (3) -20℃ DC internal resistance DCR test:
[0138] At room temperature, charge the battery with 1C constant current to 3.65V, then charge it with 3.65V constant voltage to 0.05C cutoff, and then discharge it with 1C constant current to 50% SOC. Adjust the ambient temperature to -20℃, discharge it at 0.36C for 30s, and record the discharge DC internal resistance.
[0139] (4) Cycle test:
[0140] After the lithium-ion secondary battery is left to stand for 2 days at 45°C, it is first discharged at 1C to 2.0V. Then, in an environment of 25°C, a double-sided clamp with a clamp force of 3000N is used to clamp the battery. The charging process is: 1C constant current charging to 3.65V, constant voltage 3.65V charging to current <0.5C, standing for 5 minutes, then 1C constant current charging to 3.65V, constant voltage 3.65V charging to current <0.1C, standing for 5 minutes, then 1C constant current charging to 3.65V, constant voltage 3.65V charging to current <0.05C; the discharge process is: standing for 5 minutes, 1C constant current discharge to 2.0V, and the discharge capacity at this time is recorded as the initial 1C discharge capacity; the charge and discharge cycle is performed in this way until the discharge capacity is 80% of the initial 1C constant current discharge to 2.0V capacity, and the number of cycles is recorded.
[0141] Table 1 Wettability of negative electrode sheet with electrolyte and adhesion with coated separator
[0142]
[0143] Note: The adhesion between the first negative electrode sheet and the separator is recorded as A1, and the adhesion between the second negative electrode sheet and the separator is recorded as A2.
[0144] From the test results of the liquid absorption time in Table 1, it can be seen that for the negative electrode sheet of the same formula in Comparative Example 1, the liquid absorption time of the negative electrode sheet corresponding to the inner layer of the winding core is equivalent to that of the negative electrode sheet corresponding to the outer layer of the winding core;
[0145] In Examples 1-8, the first binder corresponding to the first negative electrode sheet in the inner layer of the winding core has a higher swelling rate and a shorter liquid absorption time, which makes the electrode sheet better in wettability with the electrolyte; the second binder corresponding to the second negative electrode sheet in the outer layer of the winding core has a smaller swelling rate and a slightly longer liquid absorption time. This binder makes the electrode sheet relatively less wettable with the electrolyte, but since the diffusion distance of the electrolyte infiltration is shorter, the wettability requirements can be met.
[0146] From the adhesion test results in Table 1, it can be seen that for the same formula negative electrode sheet in Comparative Example 1, the adhesion between the negative electrode sheet and the diaphragm corresponding to the inner layer of the winding core is significantly worse than the adhesion between the negative electrode sheet and the diaphragm corresponding to the outer layer of the winding core. This is because when the battery cell is hot-pressed, the outer layer of the diaphragm is heated first, and the temperature is higher. The negative electrode binder therein forms a strong hydrogen bond interaction with the coating molecule PVDF on the glue-coated diaphragm, and the corresponding diaphragm and the electrode sheet have a stronger adhesion. It should be noted that the first binder in the first negative electrode sheet is more likely to have affinity with the electrolyte, which comes from the good affinity of its surface grafted function with the electrolyte and its more flexible molecular chain, which makes it easier for the solvent molecules in the electrolyte to enter the binder for electrolyte adsorption. The second binder in the second negative electrode sheet has a larger and longer molecular chain. Although its surface functional groups can be infiltrated with the electrolyte, its intermolecular network structure will inhibit the entry of the electrolyte solvent, resulting in a smaller electrolyte swelling rate, corresponding to a stronger structural rigidity.
[0147] The first binder corresponding to the first negative electrode sheet in the inner layer of the core in Examples 1-4 has better flexibility and is relatively easier to deform during hot pressing. It is more conducive to mutual diffusion with the PVDF molecular chains in the diaphragm and molecular chain interaction with the first binder during hot pressing, and is conducive to mechanical anchoring of PVDF and the pores of the negative electrode sheet to improve the bonding strength. Therefore, compared with Comparative Example 1, the bonding strength between the first negative electrode sheet in the inner layer of the core and the diaphragm in Examples 1-4 has been significantly improved, and the bonding strength between the inner layer of the core and the outer layer of the core is equivalent, thereby solving the technical problem of large disparity in bonding strength across the entire thickness.
[0148] The first binder in the first negative electrode sheet of the inner layer of the core in Example 5 is significantly less than that in the inner layer of Example 1, and the corresponding negative electrode sheet absorbs liquid for a longer time; while the second binder in the second negative electrode corresponding to the outer layer of the core accounts for 10% (the second binder in the outer layer of the core in Example 1 accounts for 0), and its softer second binder is conducive to improving the bonding strength during hot pressing, and the corresponding bonding strength is greater.
[0149] Table 2 Comparison of DC internal resistance and cycle performance
[0150]
[0151] It can be seen from Table 2 that compared with Comparative Example 1, the first negative electrode sheet in the inner layer of the winding core in Example 1 improves the wettability of the negative electrode sheet in the inner layer of the winding core with the electrolyte, which is more conducive to reducing the internal resistance, and the corresponding DC internal resistance at -20°C is smaller.
[0152] Compared with Comparative Example 1, the first negative electrode sheet in the inner layer of the core in Examples 1-8 improves the wettability of the negative electrode sheet in the inner layer of the core with the electrolyte, which is beneficial to reducing the internal resistance of the battery cell. The bonding effect between the negative electrode sheet and the diaphragm in the entire core package is similar, that is, the bonding strength between the first negative electrode sheet in the inner layer of the core and the diaphragm and the bonding strength between the second negative electrode sheet in the outer layer of the core and the diaphragm are almost the same, which is more beneficial to improving the problem of electrode misalignment during the cycle and is beneficial to improving the cycle performance.
[0153] In Examples 1-4, as the swelling rate corresponding to the B-type binder increases, that is, the greater the swelling rate of the B-type binder is (Example 3>Example 4>Example 1>Example 2), the better its affinity with the electrolyte, the shorter the liquid absorption time, and the better the electrolyte wettability corresponding to the corresponding first negative electrode sheet (as shown in Table 1), which is conducive to improving the diffusion of lithium ions between particles at low temperatures, thereby helping to reduce the low-temperature DC internal resistance. However, at the same time, the greater its swelling rate, the lower its corresponding polar functional group content will be, which will reduce the bonding force to a certain extent, but the B-type binder with a generally higher swelling rate has better flexibility, and the better the flexibility of the corresponding electrode sheet, the easier it is to deform at elevated temperatures, which is conducive to the mechanical anchoring effect between the PVDF molecular chain on the diaphragm and the electrode sheet, and is conducive to increasing the bonding force. Therefore, the bonding force between the corresponding first negative electrode sheet and the diaphragm is still more advantageous than that of the comparative example, which is conducive to reducing the problem of electrode sheet dislocation during the cycle, thereby improving the cycle performance.
[0154] In Example 1 and Examples 5-6, as the proportion of the type B binder with a higher swelling rate in the first negative electrode sheet increases, its affinity with the electrolyte is better, and the electrolyte wettability of the corresponding first negative electrode sheet becomes better (as shown in Table 1), which is beneficial to improving the diffusion of lithium ions between particles at low temperatures, thereby helping to reduce the low-temperature DC internal resistance.
[0155] In Example 1 and Examples 7-8, as the thickness ratio of the first negative electrode sheet corresponding to the first binder with a higher swelling rate increases, the trend of reducing the DC internal resistance is more obvious, and the corresponding ability to improve the adhesion between the negative electrode sheet and the diaphragm is increased, thereby improving the ability to prevent the electrode sheet from being dislocated, which is beneficial to improving the cycle performance.
[0156] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A battery cell, characterized in that: From the center to the edge of the battery cell, it includes the inner layer area of the battery cell and the outer layer area of the battery cell; The battery cell comprises a negative electrode sheet, a positive electrode sheet and a separator, the negative electrode sheet comprises a first negative electrode sheet and a second negative electrode sheet, the first negative electrode sheet is arranged in the inner layer area of the battery cell, and the second negative electrode sheet is arranged in the outer layer area of the battery cell; The first negative electrode sheet includes a first active material layer, and the first active material layer includes a first active material and a first binder; The second negative electrode sheet includes a second active material layer, and the second active material layer includes a second active material and a second binder; The swelling rate of the first binder is greater than the swelling rate of the second binder; The bonding force between the first negative electrode sheet and the separator is recorded as A1, and the bonding force between the second negative electrode sheet and the separator is recorded as A2. A1 and A2 satisfy the following relationship: -2≤A1-A2≤0; The first adhesive includes a Class B adhesive, or includes a Class B adhesive and a Class C adhesive; The second adhesive includes a Class C adhesive, or includes a Class B adhesive and a Class C adhesive; The mass percentage of the type B binder in the first binder is greater than the mass percentage of the type B binder in the second binder, and the swelling rate of the type B binder is greater than the swelling rate of the type C binder; The type B binder includes at least one of 2-octyl acrylate modified styrene-butadiene rubber, acrylamide modified styrene-butadiene rubber, methyl acrylate modified styrene-butadiene rubber, butyl acrylate modified styrene-acrylic rubber, acrylonitrile modified styrene-acrylic rubber, and epoxy acrylate modified styrene-acrylic rubber; The Class C adhesive includes at least one of an acrylate, acrylic acid, and acrylonitrile ternary copolymer adhesive, an acrylic acid, acrylamide, and acrylonitrile ternary copolymer adhesive, an acrylic acid, an acrylate, and an acrylamide ternary copolymer adhesive, a methyl acrylate, butadiene, acrylic acid, and acrylonitrile quaternary copolymer adhesive, and an acrylic acid, epoxypropylene, and acrylate ternary copolymer adhesive.
2. The battery cell according to claim 1, characterized in that: The swelling rate of the type B binder is 40% to 75%; The swelling rate of the C-type binder is 0% to 20%; and / or, The bonding strength between the first negative electrode sheet and the separator is 4.0 to 6.0 N / m; The bonding strength between the second negative electrode sheet and the separator is 6.0 to 8.0 N / m.
3. The battery cell according to claim 1, characterized in that: In terms of mass percentage, the first binder includes: 20% to 100% of a type B binder and 0% to 80% of a type C binder; The second adhesive includes: 0% to 55% of a type B adhesive and 45% to 100% of a type C adhesive.
4. The battery cell according to claim 1, characterized in that: In parts by mass, The first active material layer includes 95-99 parts of a first active material, 1.0-3.5 parts of a first binder, 0.5-2.0 parts of a first conductive agent, and 0-1.5 parts of a first thickener; The second active material layer includes 95-99 parts of a second active material, 0.5-3.5 parts of a second binder, 0.5-2.0 parts of a second conductive agent, and 0-1.5 parts of a second thickener; The mass percentage of the first binder in the first active material layer is greater than or equal to the mass percentage of the second binder in the second active material layer.
5. The battery cell according to claim 4, characterized in that: In parts by mass, The first active material layer includes 95-98.5 parts of a first active material, 1.0-3.0 parts of a first binder, 0.5-1.5 parts of a first conductive agent, and 0-1.2 parts of a first thickener; The second active material layer includes 95.5 to 99 parts of a second active material, 1.0 to 3.0 parts of a second binder, 0.5 to 1.5 parts of a second conductive agent, and 0 to 1.2 parts of a second thickener.
6. The battery cell according to claim 1, characterized in that: The inner layer area of the battery core accounts for 10% to 75% of the overall thickness of the battery core.
7. The battery cell according to any one of claims 1 to 6, characterized in that: The battery core is a wound battery core or a laminated battery core.
8. A battery, characterized in that: The battery comprises the battery cell according to any one of claims 1 to 7.
Citation Information
Patent Citations
Negative plate and battery
CN114597336A